Photoinduced Bending of a Large Single Crystal of a 1, 2‐Bis(4‐pyridyl)ethylene‐Based Pyridinium Salt Powered by a [2+2] Cycloaddition1. Issue 26 (21st May 2013) - Sun, Jian‐Ke; Li, Wei; Chen, Cheng; Ren, Cai‐Xia; Pan, Dan‐Mei; Zhang, Jie
<x xml:space="preserve">Abstract</x> Rolled‐up crystals: Photoinduced bending of large single crystals has been realized based on a simple organic small molecule (see picture). The bending process is accompanied with high visual fluorescence contrast, which is essential for remote detection of photomechanical work.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>